Sistem Pengarsipan Sertifikat Keahlian (SKA) dan Sertifikat Keterampilan (SKT) pada Asosiasi Tenaga Teknik Indonesia (ASTTI) Provinsi Aceh - Muzakkir Walad (KITA Institute, 2020)
The competency standard of expert / skilled personnel implementing construction services is used as a reference for everyone who intends to obtain a certificate, where relevant competence will be recognized in the field of engineering in accordance with their expertise and skills. Feasibility standards are a guideline for the Association of Indonesian Technical Personnel (ASTTI) Aceh Province in the order to the certification process for its members. Problems in this study can be formulated on how to present the Expertise Certificate (SKA) Filing System and Skills Certificate (SKT) at the Indonesian Association of Technical Personnel (ASTTI) in Aceh Province and design a web-based application. The purpose of the study was to design a Skill Certificate (SKA) and Skills Certificate (SKT) Archiving System at the Indonesian Association of Technical Personnel (ASTTI) in Aceh Province to make it faster and more accurate. The method used in the Design of Archiving System Certificate of Skills (SKA) and Skills Certificate (SKT) at the Indonesian Association of Technical Personnel (ASTTI) in the Province of Aceh is based on the waterfall method or called the waterfall method. Based on observations and authors can draw a conclusion that the Archiving System Certificate of Skills (SKA) and Skills Certificate (SKT) at the Indonesian Association of Technical Personnel (ASTTI) Province of Aceh Using Web-based is designed with the aim to replace the recording of SKA, SKT archive data and registration certification is manually computerized to minimize the level of error in recording and managing SKA, SKT archive data and certification registration data. Where this application can simplify and accelerate the time to process SKA archive data, SKT, and certification registration in terms of socialization of SKA archive data, SKT, and ASTTI certification registration. It is expected that with a computerized system to encourage employees to be more disciplined in improving employee performance in the progress of the institution.